Perawatan Mahkota Jaket Pasca Pulpotomi pada Gigi Kaninus Desidui Rahang Atas: Laporan Kasus - Muhammad Daffa Mahanna; Septriyani Kaswindiarti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Dental caries is a major problem in orodental health, especially in children. The primary cause of caries is the activity of cariogenic microorganisms. Unbalanced remineralization of dental tissue followed by destruction of organic matters may cause cumulative and progressive damage to the tooth structure. Extensive caries lesions that have reached the pulp are an indication for pulp therapy with appropriate crown restoration. Case Report: A 10-year-old boy came with a complaint of a painful cavity in his upper right front tooth. The patient was considered communicative and cooperative. The patient also had a habit of consuming sweets. An intraoral examination revealed extensive caries on the entire surface of 53. A periapical radiograph showed a radiolucent area reaching the pulp cavity on the occlusal surface of 53 with resorption of the apical one-third of the root. Based on the examination results, reversible pulpitis was established as the primary diagnosis. The treatment plan was pulpotomy with a dental crown restoration. Treatment was carried out over four visits. First visit included complete examination, periapical radiography, and pulpotomy. The second visit included core buildup, tooth preparation, and dental impressions. The third visit included try-in and crown insertion, followed by a final follow-up visit. Conclusion: Pulpotomy with dental crown restoration can be an effective clinical approach to restore the function and aesthetics of anterior deciduous teeth, especially in cases that consider aesthetics and cost limitations.